Occlusal Diagnosis and Treatment for a Patient with Unconscious Mouth Opening Disability: A Case Report - Torii, Kengo (British Journal of Healthcare and Medical Research, 2024)
An occlusal analysis was performed on a patient with unconscious mouth opening disability, and abnormal occlusion was found. Occlusal splint therapy was performed, however, this was ineffective. After that, occlusal position correcting therapy was performed, and the opening disability disappeared. As a result of occlusal analysis, it was speculated that the patient’s opening disability was due to contracture of the masticatory muscles.